2007
DOI: 10.1097/01.mcg.0000225550.26751.6a
|View full text |Cite
|
Sign up to set email alerts
|

Age and Time as Factors in the Left-to-right Shift of the Subsite of Colorectal Adenocarcinoma: A Study of 213,383 Cases From the California Cancer Registry

Abstract: The most attractive hypothesis is that a greater likelihood of prior polypectomy, and thus prevention of more cancers, occurs on the left side than on the right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 16 publications
10
76
0
4
Order By: Relevance
“…36 The mean age in the current study cohort was at least a decade younger than that of Western populations. 37 Because leftsided CRC has been reported to be associated with younger age, 38 this may possibly explain the high incidence of left-sided tumors noted in the current study population. We believe the finding that the majority of CRC cases in the current study cohort were left-sided tumors and the patients had a lower mean age at the time of diagnosis compared with Western populations can explain in part the low prevalence of BRAF noted herein and hence the low incidence of the serrated pathway compared with a Western population.…”
Section: 32mentioning
confidence: 69%
“…36 The mean age in the current study cohort was at least a decade younger than that of Western populations. 37 Because leftsided CRC has been reported to be associated with younger age, 38 this may possibly explain the high incidence of left-sided tumors noted in the current study population. We believe the finding that the majority of CRC cases in the current study cohort were left-sided tumors and the patients had a lower mean age at the time of diagnosis compared with Western populations can explain in part the low prevalence of BRAF noted herein and hence the low incidence of the serrated pathway compared with a Western population.…”
Section: 32mentioning
confidence: 69%
“…Within the colon, women have more proximal colon cancers (Svensson et al, 2002), whereas in men there is a predominance of distal colon cancer, in particular in White males; moreover, the male-to-female ratios progressively increase from the proximal colon to the distal colorectum (Wu et al, 2001). The left-to-right shift of incidence is greater among women than among men (Saltzstein and Behling, 2007). Furthermore, a more increased incidence of proximal colon cancer in women was reported early in 1983 by Beart et al(1983), and the continuing trends could be found afterwards (Obrand and Gordon, 1998).…”
Section: Genetic Pathwaymentioning
confidence: 87%
“…The male-to-female ratios progressively increased from the proximal colon to the distal colon; the ratios of proximal-to-distal CRC gradually increased with advancing age Saltzstein and Behling, 2007 California cancer registry including 213 383 cases…”
Section: Genetic Pathwaymentioning
confidence: 99%
“…The disproportionate decrease in left sided tumors have also been attributed to preference of use of sigmoidoscopy over colonoscopy because of its cost and simplicity. Due to increased use of sigmoidoscopy, majority of adenomatous polyps from the left colon are removed prior to their malignant transformation (Saltzstein et al, 2007). There seems to be an increasing trend of detection of these malignancies at an earlier stage, especially with increase in detection of Modified Duke's B.…”
Section: Discussionmentioning
confidence: 99%